Use of Marijuana to Promote Well-Being: Effects of Use and Prohibition in the Daily Lives of Brazilian Adults - Luciana Togni de Lima e Silva Surjus; Natália Cavalcante Dainesi; Felipe Granado de Souza (SAGE Publishing, 2023)
Background: Marijuana is the most widely used illicit drug worldwide. From an occupational perspective, its use is paradoxical in that although it can be harmful to health and has criminal consequences, it can also promote well-being. This study examined predictors of well-being to determine the effects of marijuana use and its prohibition on the daily lives of Brazilian adults. Methods: This cross-sectional study used an anonymous online questionnaire with a final sample of 2637 respondents. Utilizing logistic regression, variables were selected pertaining to use and prohibition risks, benefits of use, and harm reduction associated with the socioeconomic characteristics of the respondents. Results: Using marijuana for fun was most likely among those self-identified as male, trans/non-binary people, college graduates, and those with higher incomes. Living with family members and using less frequently proved to be protective against the adverse effect of "getting high." Indigenous peoples and youth were more likely to report trouble with the police due to marijuana use; individuals with higher education and longer use of marijuana reported more frequent use of harm reduction strategies; people who identified their color as yellow were more likely to report daily use compared to people who identified their color as white; women and people with higher income were less likely to report daily use. Conclusions: Social class, race, gender, and generation were predictors of well-being associated with marijuana use and its prohibition, indicating an interaction between different dimensions involving the use of illicit substances. Identifying the effects of the use and prohibition of marijuana in promoting well-being, from the conception of drug use as a non-sanctioned occupation, can broaden the understanding of this complex human phenomenon, with health and criminal repercussions, subsidizing the development of approaches more equitable and adequate into occupational therapy to reduce personal and social harm.